2021
DOI: 10.1155/2021/6685493
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Inhibitor Inhibits the Oxidative Damage Induced by Central Venous Catheter via Abolishing Focal Adhesion Kinase-Protein Kinase B Pathway Activation

Abstract: The vascular injury induced by central venous catheter (CVC) indwelling is the basis for the occurrence and development of CVC-related complications, such as phlebitis, venous thrombosis, and catheter-related infections. Focal adhesion kinase (FAK) and FAK-protein kinase B (AKT) signaling pathway are of great significance in tissue repair after trauma. Here, we investigated the role and mechanism of the FAK inhibitor (1,2,4,5-phenyltetramine tetrahydrochloride (Y15)) in oxidative damage caused by CVC. EA.hy926… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It indicated that Y15 could not only reduce CVC-induced oxidative stress injury to blood vessels but also prevent phlebitis and thrombosis caused by CVC through inhibiting the activation of FAK-AKT pathway. 8 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated that Y15 could not only reduce CVC-induced oxidative stress injury to blood vessels but also prevent phlebitis and thrombosis caused by CVC through inhibiting the activation of FAK-AKT pathway. 8 …”
Section: Resultsmentioning
confidence: 99%
“…It indicated that Y15 could not only reduce CVC-induced oxidative stress injury to blood vessels but also prevent phlebitis and thrombosis caused by CVC through inhibiting the activation of FAK-AKT pathway. 8 Wang et al also confirmed that Y15 had anti-inflammatory effects against vascular endothelial injury triggered by CVC combined with 5-FU by regulating the FAK-NF-κB signaling pathway. 9 EA.hy926 cells were randomly assigned to three groups: normal control, model group [ie, a cell inflammatory injury model induced by three scratches (2 cm each), three CVC (1 cm) segments, and 1 g/L 5-FU 80 μL], and experimental group (ie, 50 μL of 2 mmol/L Y15 was added to the model group).…”
Section: Focal Adhesion Kinase Signaling Pathwaymentioning
confidence: 90%
“…Our surgical stress model comprised the jugular central venous catheterization (CVC) and was performed according to a standardized technique 11 . CVC has previously been shown to induce oxidative stress in animal models 12 . Within the experimental groups, this procedure also enabled the parenteral infusion of LE by using a specific catheter that allowed a connection to a gyratory swivel apparatus, which ensured partial free mobility for the animals 13 …”
Section: Methodsmentioning
confidence: 99%
“…Protein kinase B (Akt) is a potential pharmacological target for the advanced‐stage SARS‐CoV‐2 infection; its inhibition will effectively suppress the pathological fibroproliferation, cytokine storm, platelet activation, and inflammation associated with COVID‐19 (Basile et al, 2021 ). Furthermore, this inhibition could prevent scarring and lung injuries (Wang, Lin, et al, 2021 ). In addition, since inhibition of Akt by pharmacologic inhibitors has also been reported to reduce ACE2 expression, a crucial receptor for the viral entry into the respiratory system cells, targeting Akt for COVID‐19 seems to be a feasible option (Somanath, 2020 ).…”
Section: Pharmacological Effects Of Genistein As a Probable Beneficia...mentioning
confidence: 99%